URBAN PLANNING AND URBAN VALUES: A JACOBSIAN ANALYSIS. Issue 2 (2021) - Ikeda, Sanford
Abstract: The great urbanist Jane Jacobs details how urban planning impacts the social interactions and social networks responsible for the economic death or life of a city. How might urban planning impinge on the moral values that underlie that development? I draw on Jacobs's work on the moral foundations of commercial society to identify two "urban values" (tolerance and innovation). I then examine how these values support the social networks and processes that facilitate urban-based innovation and how urban planning can strengthen or undermine those values. I use the examples of urban planning in the 15 th Ward of Syracuse, New York and of city building in the private development of Cayalá in Guatemala City to illustrate these points.